Legal Implications of Evidence Removal by Police: the Barelang Case Study - Riza, Khairul; Lubis, Irpan Husein (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This study aims to analyze the legal implications of evidence tampering or disappearance by law enforcement officers in the criminal justice process, with a specific focus on the Polresta Barelang case in Batam, Indonesia. It finds that evidence tampering undermines institutional accountability and erodes public trust in law enforcement and the judiciary. The study emphasizes the need for stronger oversight mechanisms and transparent evidence management policies to restore integrity in the criminal justice system. Methodology/approach: The research employs a socio-legal approach (normative-empirical method), combining statute and case approaches. Primary data were collected through interviews with law enforcement officers, representatives from the Financial Transaction Reports and Analysis Center (PPATK), and civil society actors. Secondary data were obtained from books, journal articles, laws, court decisions, and official documents from the Batam Free Trade Zone Authority. The data were analyzed using a qualitative-descriptive method with a regulatory and field-practice analysis. Results/findings: The study reveals that the removal of evidence by police officers severely undermines due process and violates criminal procedure law and professional ethics. The case at Polresta Barelang highlights systemic weaknesses in internal accountability mechanisms, low transparency, and a lack of external oversight. Conclusions: The findings confirm the urgent need for regulatory reform, institutional accountability, and the implementation of digital-based evidence tracking systems. Addressing these issues is essential to safeguard the fairness of judicial proceedings and rebuild public confidence. Limitations: This study is limited to one regional police institution and does not encompass nationwide patterns of evidence management across law enforcement bodies. Contribution: The study provides critical insight into criminal justice reform, particularly in strengthening evidence management systems. It is relevant for policymakers, legal academics, anti-corruption bodies, and institutions responsible for law enforcement accountability.